Law and practice on public participation and access to justice in environmental matters in Trinidad and Tobago and Jamaica - Mohammed, N.J. (2018)
In 1992, Caribbean states were among over 150 states, who adopted, by consensus, the Rio Declaration on Environment and Development. Principle 10 of that Declaration emphasises the role of participatory rights at a national level in the achievement of the goal of sustainable development. It articulates what are now commonly referred to as the three ‘pillars’ of procedural participation in environmental matters: access to information, public participation in decision-making and access to justice.